Structural analyses of the AAA+ ATPase domain of the transcriptional regulator GtrR in the BDSF quorum‐sensing system in Burkholderia cenocepacia. Issue 1 (7th December 2021) - Yan, Xin‐Fu; Yang, Chunxi; Wang, Mingfang; Yong, Yonlada; Deng, Yinyue; Gao, Yong‐Gui
Abstract : Global transcriptional regulator downstream RpfR (GtrR) is a key downstream regulator for quorum‐sensing signaling molecule cis‐2‐dodecenoic acid (BDSF). As a bacterial enhancer‐binding protein (bEBP), GtrR is composed of an N‐terminal receiver domain, a central ATPases associated with diverse cellular activities (AAA+) ATPase σ 54 ‐interaction domain, and a C‐terminal helix‐turn‐helix DNA‐binding domain. In this work, we solved its AAA+ ATPase domain in both apo and GTP‐bound forms. The structure revealed how GtrR specifically recognizes GTP. In addition, we also revealed that GtrR has moderate GTPase activity in vitro in the absence of its activation signal. Finally, we found the residues K170, D236, R311, and R357 in GtrR that are crucial to its biological function, any single mutation leading to completely abolishing GtrR activity. Abstract : Global transcriptional regulator downstream RpfR (GtrR), a bacterial enhancer‐binding protein (bEBP), is a key downstream regulator for the quorum sensing signaling molecule cis‐2‐dodecenoic acid (BDSF) in Burkholderia cenocepacia . In this work, we present the structures of its AAA+ ATPase domain in both apo and GTP‐bound forms. The structural and biochemical data reveal how GtrR specifically utilizes GTP and regulates the swarming motility of B .  cenocepacia cells.